Emergency room closed reduction versus in situ splinting in the treatment of paediatric supracondylar humerus fractures. (June 2019) - Sylvia, S. M.; Maguire, K. J.; Molho, D. A.; Levens, B. J.; Stone, M. E.; Hanstein, R.; Schulz, J. F.; Fornari, E. D.
Abstract: Purpose: Displaced supracondylar humerus fractures are treated with open or closed reduction and percutaneous pinning. In 2012, our management of patients with a displaced fracture changed from closed reduction in the emergency department (ED) to in situ splinting prior to closed reduction and pinning in the operating room (OR). The purpose of this study was to investigate if outcomes or complications differ between these two management methods. Methods: Patients less than ten years old with a Gartland type II or III supracondylar humerus fracture between 2008 and 2016 were included. Cases of polytrauma were excluded. Radiographic outcomes were assessed at follow-up. The Fisher's exact test was used for categorical variables and the Wilcoxon rank sums tests for continuous variables. Results: In all, 157 patients were included, 89 with reduction in the ED and 68 without. There was no significant difference between the groups related to demographic factors or fracture characteristics. Patients managed without reduction in the ED had a lower average delay from ED to OR compared with those treated with reduction (16 hours versus 22 hours, p < 0.005) and a shorter hospital length of stay (34 hours versus 40 hours, p < 0.005). Conclusion: No difference in complications or outcomes was found between patients with Type II or III supracondylar fractures treated initially with or without closed reduction in the ED. Patients treated without ED reduction were taken to the OR sooner and remained in the hospital for a shorter period of time. Splinting in situ reduces anaesthesia exposure without increasing postoperative complications or suboptimal outcomes. Level of Evidence: Level III, retrospective comparative study